The Effects of Grazing Pressure on The Body Weight Gain and Pasture Performance - Rakhmat ,; A.I. Mappakaya; Mappaona . (Buletin Ilmu Makanan Ternak, 1991)
In order to get information on the influence of grazing pressure on the body weight gain of Bali Cattle and pasture performance, nine Bali cattle were used in the experiment conducted at Mini Ranch in Barru, South Sulawesi. The area was divided into three plots with different stocking rate i.e. Plot A = 1.0 head/ha; Plot B = 1.5 heads/ha and Plot C = 2 heads/ha. Three cattles as replication, were placed in each plot. Research results showed that the higher the stocking rate the lower the daily weight gain (DWG) (P<0.05). The carrying capacity tended to be lower with the increase of stocking rate, and the botanical composition also changed with stocking rate.